Some Milk Production and Reproductive Traits of Holstein Cattle Raised in Different Regions of Turkey - Gurses, Murad; Bayraktar, Metin (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
The objective of this study was to detect milk production and reproductive traits of Holstein breed raised in different regions of Turkey, to investigate effects of some environmental factors on these traits. For this purpose, production records were collected digitally from herd management programme of milking management systems of agricultural enterprises from Holstein cows raised in different geographical regions of Turkey. Total 8091 reproduction and 18470 milk yield records from 7623 lactation of 3550 cows raising in Ceylanpinar, Dalaman, Kocas ye Tahirova agricultural enterprises were used. The Effects of environmental factors on milk and reproductive traits were determined by the least square methods. Least square means for 100 days milk yield 2719.66 +/- 13.52, 200 days milk yield 5246.94 +/- 25.69, 305 days milk yield 7395.35 +/- 45.75 kg, first calving age 809.32 +/- 2.07 days, open days 127.43 +/- 5.41 days, calving interval 395.86 +/- 2.58 days were found. The effects of all factors (enterprise, calving year, calving season, calving age and lactation number) were found significant on 100, 200, 305 days milk yield (P<0.001). The effects of enterprise, calving year and calving season were found significant on first calving age (P<0.01). While the effect of calving year was not found significant, the effects of enterprise, calving season, calving age and lactation number were found significant on open days (P<0.05). The effects of all factors were found significant on calving interval (P<0.001). Significant differences were found for the milk production and reproductive traits between Holstein cows raised in different geographical regions of Turkey. These differences were based on climatic and administrative differences between enterprises as well as genetic factors.
Türkiye'de farklı bölgelerde yetiştirilen Holştayn sı?ırlarda bazı süt ve döl verimi özellikleri
Keywords: Holstein; Milk yield; Reproductive traits; Environmental factors; Milking system; Herd management